Visual impairment as a possible precursor symptom of Marchiafava–Bignami disease. Issue 4 (26th August 2013) - Oji, Yutaka; Tanaka, Ryota; Takanashi, Masashi; Shimura, Hideki; Hattori, Nobutaka
Abstract Marchiafava–Bignami disease is a rare, alcohol‐associated disease that primarily involves corpus callosum demyelination. As these corpus callosum lesions increase in size, they can affect the optic chiasm, optic tract and other white matter regions. Here, we report a case that includes the autopsy findings in a 53‐year‐old man diagnosed with Marchiafava–Bignami disease. The patient developed a visual impairment that preceded a consciousness disturbance by 6 months. Histopathological examination showed optic tract, deep white matter and corpus callosum involvement. Although Marchiafava–Bignami disease can affect the optic tract, visual impairment is not reported as an initial symptom of Marchiafava–Bignami disease. We propose that visual impairment in patients with chronic alcohol abuse might be an early symptom of Marchiafava–Bignami disease.